Evaluation of Serum Zinc, Copper, and Hematological Parameters (Hemoglobin, Total Leukocyte Count, Neutrophil-to-Lymphocyte Ratio) in Acne Vulgaris: A Case-Control Study - Aneela Gillani, Maria Farid, Muhammad Zubair, Sana Younas, Aisha Malik, Abdul Sadiq, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Serum zinc and copper concentrations along with hematological markers—hemoglobin, totaleukocyte count (TLC), and neutrophil-to-lymphocyte ratio (NLR)—were investigated to assesstheir associations with acne vulgaris in a case-control design